1988
DOI: 10.1136/gut.29.9.1229
|View full text |Cite
|
Sign up to set email alerts
|

Employment problems and prospects for patients with inflammatory bowel disease.

Abstract: Executive, MerseysideŜ UMMARY A random sample of 170 patients (88 men) with chronic inflammatory bowel disease (75 ulcerative colitis) were first interviewed in 1978 about their employment status, problems at work, and influence of surgery. Surgery had been carried out on 120 and 53 had an ileostomy. After six years 144 (92%) ofthe 156 survivors replied to a follow up postal questionnaire. Of the initial sample, 122 (72%) were working and there were only three (1%) registered unemployed. After six years a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 9 publications
3
41
0
Order By: Relevance
“…Yet most studies show that patients want more information-". Wyke et al 6 found advice on employment lacking in particular. They felt that although hospital specialists should give this information, shortage of time, changes of staff and the presence in clinics of relatively untrained juniors meant that gastrointestinal nurse counsellors may be the best solution to this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Yet most studies show that patients want more information-". Wyke et al 6 found advice on employment lacking in particular. They felt that although hospital specialists should give this information, shortage of time, changes of staff and the presence in clinics of relatively untrained juniors meant that gastrointestinal nurse counsellors may be the best solution to this problem.…”
Section: Discussionmentioning
confidence: 99%
“…However, if indirect costs were captured, the model would likely demonstrate an even greater increase in costs for each disease state as previous research has indicated that CD has a negative effect on employment, 24 and as disease severity increases, work absences increase and productivity decreases. 25 For example, a study of an international population of patients with moderate-to-severe active CD revealed that 39% were unemployed and 25% were receiving disability benefits. 26 In addition, a study by Lichtenstein et al 27 demonstrated that disease remission, measured using the Crohn's disease activity index, was associated with improvement in employment status and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan these disease are classified as nanbyou , a Japanese word that refers to 1 diseases without known causes and 2 diseases that place a continuous burden on the patient and his her family, not just in economic terms but also with regard to 2002 Wyke et al, 1988 , and that these differences are related to the presence or absence of their symptoms Longobardi et al, 2003 . Questions were designed to evaluate the frequency with which a patient experienced difficulties. Patients were asked to choose from one of the following 3 possible answers for each item never , sometimes , or often .…”
Section: Introductionmentioning
confidence: 99%